A tunable comb filter using single-mode/multimode/polarization-maintaining-fiber-based Sagnac fiber loop - 阮隽 张伟刚 张昊 耿鹏程 白志勇 (Chinese physics B, 2013)
A novel tunable comb filter composed of a single-mode/multimode/polarization-maintaining-fiber-based Sagnac fiber loop is proposed and experimentally demonstrated. The filter tunability is achieved by rotating the polarization controller. The spectral shift is dependent on rotation direction and the position of the polarization controller. In addition, the adjustable range achieved by rotating the half-wave-plate polarization controller is twice higher than that of the quarter-wave-plate one.